DESIGNING ICT COMPETENCES-INTEGRATED SYLLADESIGNING ICT COMPETENCES-INTEGRATED SYLLABUSES OF READING COURSES (DESIGN AND DEVELOPMENT STUDY OF ENGLISHBUSES OF READING COURSES (DESIGN AND DEVELOPMENT STUDY OF ENGLISH LANGUAGE EDUCATION PROGRAM SYLLABUSES) - Bandan, Aldo Prabowo; Dewanti, Ratna (IJLECR (International Journal of Language Education and Cultural Review), 2019)
ICT education provides the unlimited resources to collect and analyze data, create presentation using ICT tools and acquire depth of knowledge. This research aims to design ICT competence-integrated syllabuses of reading courses (Literal Reading, Critical Reading, Affective Reading, and Syntopical Reading). The types of syllabus for reading courses in this research is process-oriented syllabuses. This research adapted Design and Development Research (DDR). The stages of DDR are need analysis, evaluation, revision, and evaluation. An analysis was also conducted the CEFR-based English reading to provide language learners a set of language qualification to master. The data sources to analyze existing English reading syllabuses were taken from five different universities in Indonesia. The result of sub RQ 1 found that the ICT competences are mostly integrated in teaching methods, and assessments. For the ICT tools in the existing syllabus mostly used computer, laptop, LCD, word and presentation software. UNESCO competence in the existing syllabus mostly integrated implicitly and explicitly in technology literacy. Learning processes mostly appear in the existing syllabus were identifying, discussing, and analyzing. Sub RQ 2 found the integration of ICT into syllabus component can be applied by infusing the ICT indicator into the syllabus components, and the integration of CEFR into learning materials to see the levels of the students. Sub RQ 3 found designing ICT competences-integrated syllabuses of reading courses used process-oriented for the type of syllabus. The components of syllabus that integrated in reading syllabuses were course description, learning outcomes, learning objective, materials, teaching method, assessments, and resources. Keywords: ICT competences, English reading syllabuses, CEFR for languages.